Remission of screen-detected metabolic syndrome and its determinants: an observational study - den Engelsen Corine; Gorter Kees J; Salomé Philippe L; van den Donk Maureen; Rutten Guy E (BMC, 2012)
Abstract Background Early detection and treatment of the metabolic syndrome may prevent diabetes and cardiovascular disease. Our aim was to assess remission of the metabolic syndrome and its determinants after a population based screening without predefined intervention in the Netherlands. Methods In 2006 we detected 406 metabolic syndrome cases (The National Cholesterol Education Program's Adult Treatment Panel III (NCEP ATP III) definition) among apparently healthy individuals with an increased waist circumference. They received usual care in a primary care setting. After three years metabolic syndrome status was re-measured. We evaluated which baseline determinants were independently associated with remission. Results The remission rate among the 194 participants was 53%. Baseline determinants independently associated with a remission were the presence of more than three metabolic syndrome components (OR 0.46) and higher levels of waist circumference (OR 0.91), blood pressure (OR 0.98) and fasting glucose (OR 0.60). Conclusions In a population with screen-detected metabolic syndrome receiving usual care, more than half of the participants achieved a remission after three years. This positive result after a relatively simple strategy provides a solid basis for a nation-wide implementation. Not so much socio-demographic variables but a higher number and level of the metabolic syndrome components were predictors of a lower chance of remission. In such cases, primary care physicians should be extra alert.